Biflustra perambulata n. sp. (Cheilostomata: Bryozoa), a new alien species from Cochin Harbour, Kerala, India - Louis, Soja; Menon, N. R. (Zootaxa, 2009)
During a study of the Bryozoa of Cochin Harbour, Biflustra perambulata n. sp. (Membraniporidae) was discovered at an oil-tanker berth. Two erect foliaceous and brittle colonies of the species were found attached to a wooden rack deployed to suspend test coupons to collect fouling bryozoans. The present record documents the recruitment to this harbour of a genus most naturally occurring in geographically distant localities. Insofar as a number of Biflustra species are known to be distributed via shipping to contiguous waters, the new species is interpreted to be an alien introduction, with a probable provenance from South-East Asia via a merchant vessel.